No association between the vitamin D pathway gene polymorphisms and bone biomarkers response to calcium and low dose calcitriol supplementation in postmenopausal Chinese women: a one-year prospective study. (3rd October 2018) - Gu, Jiemei; Wang, Chun; Zhang, Hao; Yue, Hua; Hu, Weiwei; He, Jinwei; Fu, Wenzhen; Zhang, Zhenlin
Abstract: Introduction: The aim of the study was to explore the association between the vitamin D pathway gene variations and the bone biomarkers response to calcium and low dose calcitriol supplementation in postmenopausal Chinese women. Methods: A total of 110 healthy postmenopausal Chinese women (61.51 ± 6.93 years) were enrolled. The participants were supplemented with calcium (600 mg/d) and calcitriol (0.25 μg/d), for 1 year. Four biomarkers, serum levels of beta C-terminal cross-linked telopeptides of type I collagen (β-CTX), amino-terminal propeptide of type I collagen (P1NP), parathyroid hormone (PTH) and 25-hydroxyvitamin D [25(OH)D] were measured at baseline and 12-month follow-up. Multivariate regression models were established to explore the statistical association between the change rate of the four biomarkers and 15 key genes within the vitamin D metabolic pathway. Results: This exclusion process left 98 participants for analysis. Serum levels of P1NP, β-CTX and PTH were significantly decreased at the 12-month follow-up (all p < 0.05). Serum 25(OH)D level had no significant change ( p > 0.05). No association was found between the vitamin D pathway gene polymorphisms and bone biomarkers response to calcium and low dose calcitriol supplementation. Conclusions: Genetic background of postmenopausal Chinese women might not influence supplemental response of the biomarkers to calcium and low dose calcitriol.